POTENTIAL DEMARKETING STRATEGY APPLICATION IN ELECTRIC POWER CONSUMPTION RATIONALZATION: A FIELD STUDY IN ADEN, YEMEN - Al-Hazmi, Nabil Mohemmed (CENTRAL ASIA AND THE CAUCASUS, 2021)
This research aims to investigate potential demarketing alternatives towards rationalizing electricity consumption in Aden, Yemen. A descriptive-analytical method was employed to attain the study objectives and evaluate the research hypothesis with questionnaires distributed to 400 study samples. Resultantly, a relationship was identified between demarketing strategy implementation and electricity consumption rationalization in Aden, Yemen. Additionally, this research proposed a programmed and phased utilization of demarketing strategies and enhancing awareness and educational programs towards electricity consumption rationalization with various social media platforms in the Aden Governorate.